Association of suicidality, sleep duration, screen time, and social behaviors among U.S. adolescents - Shuo Feng; Renming Liu; Aditi Tomar; Ping Ma (New Prairie Press, 2024)
Suicide is a leading cause of death among U.S. adolescents. Short sleep duration and screen time were potential risk factors. This study aims to explore both direct and indirect associations of screen time, sleep, and suicidality. Using the 2019 Youth Risk Behavior Survey data (N=13,677), logistic regression was conducted to examine direct associations of sleep, screen time, and suicidality when controlling demographics and social behaviors. The bootstrapping method was used to test the mediation effects of sleep. Adolescents with excessive screen time (internet, social media) have higher odd ratios in suicide ideation (OR: 1.47, 95% CI: 1.34-1.36, p. The association between screen time and suicidality is multifaceted. Excessive screen time (internet, social media) is directly associated and indirectly associated through sleep with suicidality. Future research could focus on sex differences in the associations.